Embodiment in Brain-Computer Interaction - O'Hara, Kenton; Sellen, Abigail; Harper, Richard (ACM Conference on Human Factors in Computing Systems, 2011)
With emerging opportunities for using Brain-Computer Interaction (BCI) in gaming applications, there is a need to understand the opportunities and constraints of this interaction paradigm. To complement existing laboratory based studies, there is also a call for the study of BCI in real world contexts. We present such a real world study of a simple BCI game called MindFlex®, played as a social activity in the home. In particular, drawing on the philosophical traditions of embodied interaction, we highlight the importance of considering the body in BCI and not simply what is going on in the head. The study shows how people use bodily actions to facilitate control of brain activity but also to make their actions and intentions visible to, and interpretable by, others playing and watching the game. It is the public availability of these bodily actions during BCI that allows action to be socially organised, understood and coordinated with others and through which social relationships can be played out. We discuss the implications of this perspective and findings for BCI.